2002
DOI: 10.3141/1785-04
|View full text |Cite
|
Sign up to set email alerts
|

Allocating Track Maintenance Costs on Shared Rail Facilities

Abstract: Railroads were originally conceived as public highways on which anyone might operate. This idea rapidly demonstrated its impracticality, and for many years railroads in most of the world have controlled both infrastructure and operations. However, the European Union is moving toward an open access model for railroads in which track ownership (and related functions, such as train dispatching) is required to be separate from train operations. Separate ownership and operations will require some method for establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Lopez-Pita (2001) tried to weight the cost share fairly between passenger service and freight operation by considering the proportion of wear and tear and speed differentiation. Resor and Patel (2002) suggested that a cost allocation model might be used to derive the fair share of maintenance costs of a shared asset. The authors, using a model they have developed for Conrail, argued that the incremental costs of passenger services are large and the share of maintenanceof-way cost for freight should be much smaller than what AMTRAK has estimated.…”
Section: Shared Responsibilitiesmentioning
confidence: 99%
“…Lopez-Pita (2001) tried to weight the cost share fairly between passenger service and freight operation by considering the proportion of wear and tear and speed differentiation. Resor and Patel (2002) suggested that a cost allocation model might be used to derive the fair share of maintenance costs of a shared asset. The authors, using a model they have developed for Conrail, argued that the incremental costs of passenger services are large and the share of maintenanceof-way cost for freight should be much smaller than what AMTRAK has estimated.…”
Section: Shared Responsibilitiesmentioning
confidence: 99%
“…Generally, train speed is decreased and other restrains are brought, however this method is economically ineffective. Railway road and rolling stock technical level can be effectively improved only by huge investments to the modernization of the mentioned economy [2,6,8].…”
Section: Present Situationmentioning
confidence: 99%
“…These causative factors are driven both by regulatory requirements and the specific environmental and physical track and roadway degradation relationships. The alternative to informed local engineering judgment is the use of well-known model approaches, such as the speed factored gross ton (SFGT) model form and the weighted system average cost (WSAC) model form (9). Whether the use of the SFGT and WSAC models is appropriate depends on whether or not either model form can be successfully applied to the terminal railway case.…”
Section: Keeping It Simplementioning
confidence: 99%